SCHOOL MONITORING - Santos, Andrey (CIPEEX, 2024)
THE "SCHOOL MONITORING" SOFTWARE IS AN INNOVATIVE PROPOSAL THAT AIMS TO MONITOR THE STUDENT'S SCHOOL BEHAVIOR. IT OFFERS FACILITIES SUCH AS VIEWING GRADES AND A REAL-TIME CHAT FOR PARENTS OR GUARDIANS TO CONTACT EDUCATORS AT ANY TIME. THIS WORK INVOLVED RESEARCH AND INTERVIEWS WITH PARENTS AND EDUCATORS, AS WELL AS A PRESENTATION AT SINACEN OF THE UNIVERSITY CENTER OF ANÁPOLIS. THE MAIN OBJECTIVE IS TO ALLOW PARENTS OR GUARDIANS TO BE MORE AWARE OF THEIR CHILDREN'S BEHAVIOR AT SCHOOL, FACILITATING THE MAKING OF APPROPRIATE DECISIONS. THE "SCHOOL MONITORING" ALSO AIMS TO BRING PARENTS AND EDUCATORS CLOSER TOGETHER AND INFORM PARENTS ABOUT THE DIFFICULTIES THEIR CHILDREN MAY ENCOUNTER IN SCHOOL LIFE. FOR THE DEVELOPMENT OF THE APPLICATION, WE USED A USER-CENTERED APPROACH, CONDUCTING RESEARCH WITH PARENTS AND EDUCATORS TO UNDERSTAND THEIR NEEDS AND CHALLENGES. BASED ON THIS INFORMATION, WE CREATED A SET OF REQUIREMENTS AND FUNCTIONALITIES. WE CHOSE THE AGILE SCRUM METHODOLOGY AND HELD MEETINGS WITH THE TEAM TO DECIDE ON THE BEST FEATURES FOR THE APPLICATION'S MVP. DESPITE THE EXISTENCE OF SIMILAR APPLICATIONS ON THE MARKET, OUR PROPOSAL BRINGS AN INNOVATION: IT ALLOWS PARENTS OR GUARDIANS TO BE AWARE OF THEIR CHILD'S BEHAVIOR AND DIFFICULTIES, ENABLING THEM TO TAKE THE BEST MEASURE TO SOLVE THESE SITUATIONS. THE INTERVIEWS MADE IT CLEAR THAT OUR AUDIENCE WANTS TO KNOW RECURRENTLY HOW THEIR CHILD IS BEHAVING AT SCHOOL AND IF THEY ARE FACING ANY DIFFICULTY, EITHER IN ACTIVITIES OR IN RELATION TO OTHER COLLEAGUES.